ANALISIS PENGARUH LOYALITAS MEREK DAN PREFERENSI MEREK TERHADAP NIAT PEMBELIAN ULANG SMARTPHONE PADA GENERASI Z - Sofia, Adelia Azka; Hartono, Arif (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.08.TAHUN.2022, 2022)
The study aims to examine students repurchase intentions on smartphone brands.  The population used in this study was Indonesian students who used smartphones and once bought back their smartphones. The study used primary data and used purposive sampling techniques in sampling. The number of samples collected was as many as 156 student respondents. The analysis test was conducted using the SEM method and data process using Smart PLS software. The results of the data analysis successfully showed all five significant hypotheses. (1) Brand Engagement in Self-Concept positively affects Brand Loyalty, (2) Value Consciousness positively affects Brand Loyalty, (3) Brand Loyalty positively affects Repurchase Intentions, (4) Self-Congruity positively affects Brand Preferences, (5) Brand Preferences positively affect Repurchase Intentions. The results of this research are expected to help marketers in developing any aspect that can foster the intention of buying smartphone brands in Indonesia among students.